Innovative marketing strategies in entrepreneurship - Margarita Išoraitė (Entrepreneurship and Sustainability Issues)
The article analyses the innovative marketing strategies in entrepreneurship, focusing on guerrilla marketing and examining its tools and case studies. Guerrilla marketing is a strategy in which small businesses use creativity to compete with bigger companies. The main focus is on bold, modern ideas, and investing not money but time, energy, imagination, and information is encouraged. The author suggests an original guerrilla marketing model and reveals the peculiarities of guerrilla marketing approaches. The findings can help companies design innovative marketing strategies